Task-Related Hemodynamic Response Alterations During Slacklining: An fNIRS Study in Advanced Slackliners - Seidel-Marzi, Oliver; Hähner, Susanne; Ragert, Patrick; Carius, Daniel (Frontiers in Neuroergonomics, 2021)
The ability to maintain balance is based on various processes of motor control in complex neural networks of subcortical and cortical brain structures. However, knowledge on brain processing during the execution of whole-body balance tasks is still limited. In the present study, we investigated brain activity during slacklining, a task with a high demand on balance capabilities, which is frequently used as supplementary training in various sports disciplines as well as for lower extremity prevention and rehabilitation purposes in clinical settings. We assessed hemodynamic response alterations in sensorimotor brain areas using functional near-infrared spectroscopy (fNIRS) during standing (ST) and walking (WA) on a slackline in 16 advanced slackliners. We expected to observe task-related differences between both conditions as well as associations between cortical activity and slacklining experience. While our results revealed hemodynamic response alterations in sensorimotor brain regions such as primary motor cortex (M1), premotor cortex (PMC), and supplementary motor cortex (SMA) during both conditions, we did not observe differential effects between ST and WA nor associations between cortical activity and slacklining experience. In summary, these findings provide novel insights into brain processing during a whole-body balance task and its relation to balance expertise. As maintaining balance is considered an important prerequisite in daily life and crucial in the context of prevention and rehabilitation, future studies should extend these findings by quantifying brain processing during task execution on a whole-brain level.